Modelo de múltiplas branas esféricas como uma descrição cosmológica - Jardim, Ivan Carneiro (2012)
The general solution of Einstein’s gravity equation in D dimensions for an anisotropic and spherically symmetric matter distribution is calculated in a bulk with position dependent cosmological constant. Results for n anisotropic concentric (D−2)−branes with arbitrary mass, radius and pressure with different cosmological constant between branes are found. It is shown how the difference between the cosmological constant contributes to the effective mass of each brane, and it is also shown that the equation of state for each brane influences the dynamics of branes, which can be divided into eras according to the dominant matter. This scenario can be used to model the universe in the D=5 case, which may presents a phenomenology richer than the current models. The evolution law of the branes is studied, and the anisotropic pressure that remove divergences is found. An analyze of the equation of motion allowed us to build an oscillating universe model. By an introduction of a cutoff in the density we propose a low-entropy nonsingular Big Bang model, which is consistent with the observational data. In this model we obtain the initial value of entropy, mass and acceleration of universe in terms of the maximum density.